Performance Profile of Students in High School Physics Practicum on Temperature and Heat Material - Ayuhan, Dwitya; Bunawan, Wawan (Holistic Science, 2024)
Performance profiling represents a set of strategies for the application of knowledge, skills, and work habits through the performance of meaningful and interesting tasks for students. This study aims to profile the performance of students in a high school physics practicum on temperature and heat. This performance profile provides teachers with information on the extent of students' performance abilities in conducting a physics practicum by developing performance assessment instruments that have been tested for validity, reliability, and practicality. The research was conducted in high school with the research subjects of teachers and students of the XI Physics Specialization. The results of the instrument validity test are 0.75, with a valid category. The average result of reliability with the Alpha Cronbach method in the initial test obtained a value of 0.761, and in the second test, it amounted to 0.75. The instrument is declared practical according to the assessment of the physics teacher's response to the instrument trial, which shows a value of 93%, which is in the very good category. So it can be concluded through several stages of testing that the performance assessment instrument can be used properly by students and teachers.